PENGARUH EXPERIENTIAL MARKETING DAN CITRA MEREK TERHADAP KEPUASAN PENUMPANG KERETA API BISNIS - Yasintha Soelasih (Universitas Mercu Buana, 2016)
Abstract. The changes of railway management began in 2009 have brought manyimpact on train service both long distance train or commuter. These changes have animpact on the experience felt by passengers when using the train. And the image of thetrain has also changes executives, business or economics train. The changes made willhave an influence on consumer satisfaction. Therefore, it is interesting to do researchwith the theme of experiential marketing and brand image to satisfaction of trainpassenger on the railway business, especially in Java. Number of samples in this studyconsist of 400 respondents, with a simple random sampling. The results of reliabilityand validity testing on instrument it is reliable and valid. There are three hypothesestested, using structural equation modeling. The results of hypothesis test shows that thebrand image of the train has no effect on passenger satisfaction, while experientialmarketing test has an effect on passenger satisfaction of railway business.